Rotinas produtivas e relação com as fontes no rádio informativo em ambiente de convergência: um estudo de caso de emissoras de Porto Alegre - Rutilli, Marizandra (2014)
This research has as its ultimate goal the study of sources in converging environment. To do this we chose as empirical research objects, informative stations in Porto Alegre / RS; Bandeirantes AM radios, Gaucha and Guaiba. In order to meet our goals we adopted our methodological strategies, which include the combined use of Newsmaking Theory as a theoretical and methodological approach, a comparative multiple case study, semi-structured interviews with professionals who are daily engaged in the production of news in the stations, and visualizations of productive routines. Our theoretical revisions include sociological paradigms and the construction of news (following a chronological order, a historical-conceptual route), radio and journalistic sources in convergent scenario. With the passing of our theoretical references, data obtained in the field research, we reflect on the information flow, font setting for radio and sources in converging environment indicating interference in information and communication technologies especially in relation to contact facilities between journalists and sources in on-line spaces. From our reflections we propose an updating and adjustment of some categories presented by Pinto (2000), applied to the scenario of convergence in relation to the sources, the dialogues and interference levels according to visibility allowed by digital technologies and platforms.